Primary Peritoneal Carcinosarcoma in a Breast Cancer Patient Harboring a Germline BRCA2 Pathogenic Variant: Case Report - Luciana Beatriz Mendes Gomes; Renata Lazari Sandoval; Camila Bragança Xavier; Tatiana Strava Correa; Raquel Midori Koga Matuda; Zenaide Silva de Souza; Luiz Guilherme Cernaglia Aureliano de Lima; Mariana Petaccia de Macedo; Filomena Marino Carvalho; Daniele Assad Suzuki (Case Reports in Oncology, 2024)
Malignant mixed müllerian tumor (MMMT) is a rare neoplasm, consisting of carcinomatous (epithelial) and sarcomatous (mesenchymal) components that most commonly arise in the endometrium and more infrequently in the ovaries, fallopian tube, cervix, and vagina. Primary peritoneal carcinosarcoma (PPCS) is an extremely rare extragenital presentation of MMMT. Although the occurrence of breast cancer and epithelial ovarian carcinoma in association with BRCA pathogenic variants is firmly established, the etiologic role of these genes in the development of other tumor types is less well known. Here, we present a rare case of PPCS in a 42-year-old Brazilian woman with a BRCA2 pathogenic variant, c.2808_2811del (NM_000059.3). The patient developed metastatic breast cancer at the age of 37 and underwent a risk-reducing bilateral salpingo-oophorectomy 2 years later. She was then diagnosed with PPCS 3 years after the risk-reducing surgery. She underwent treatment with surgery, chemotherapy, and targeted therapy but passed away almost 5 years after the second primary tumor diagnosis. To our knowledge, this is the first case of peritoneal carcinosarcoma described in a BRCA2 pathogenic variant carrier, and its report leads to a better understanding of the disease’s molecular features and possible therapeutic approaches.